A review of literature supporting the development of practice guidelines for teledermatology in Australia. (30th March 2020) - Abbott, Lisa M; Miller, Robert; Janda, Monika; Bennett, Haley; Taylor, Monica L; Arnold, Chris; Shumack, Stephen; Soyer, H Peter; Caffery, Liam J
Abstract: Despite the potential of teledermatology to increase access to dermatology services and improve patient care, it is not widely practised in Australia. In an effort to increase uptake of teledermatology, Australian‐specific practice guidelines for teledermatology are being developed by the Australasian College of Dermatologist. This paper reports finding from literature reviews that were undertaken to inform the development of these guidelines. Results cover the following sections: Modalities of teledermatology; Patient selection and consent; Imaging; Quality and safety; Privacy and security; Communication; and Documentation and retention. The document educates providers about the benefits and limitations of telehealth while articulating how to enhance patient care and reduce risk when practicing teledermatology.